Natural Deep Eutectic Solvents (NADES) to Enhance Berberine Absorption: An In Vivo Pharmacokinetic Study - Sut, Stefania (Molecules, 2017)
In the present study results related to the in vivo administration of Natural Deep Eutectic Solvents (NADES)-solubilized berberine are reported for the first time. NADES are mixtures of small natural compounds having a melting point significantly lower than that of any individual component. Such solvents have gained much attention of the scientific community in the green chemistry area, being considered useful alternatives to common organic solvents. NADES can be used also as administration vehicles, and this can be attractive for nutraceutical products when eutectics are formed with food grade ingredients. In this work, different NADES were prepared using mainly food grade constituents and were tested as solvents for the alkaloid berberine. Three selected NADES/berberine solutions and an aqueous suspension were orally administered to mice with in dose of 50 mg/Kg. Blood levels of berberine were measured by a LC-MS/MS method. The pharmacokinetic analysis revealed a 2–20 fold increase in blood concentration of NADES/berberine with significant changes in pharmacokinetic profile. Natural Deep Eutectic Solvents may thus be considered attractive solubilizing agents and may also play a role in the increase of absorption of poorly bioavailable natural products such as berberine.